Trends of Hadith Studies in Artificial Intelligence Research Works on Google Scholar: A Literature Review - Prayogi, Ananda (Proceedings of International Conference on Islamic Civilization and Humanities, 2023)
This literature review explores the research on Artificial Intelligence (AI) in hadith studies worldwide. Data from AI-related research publications on hadith between 2019 and 2023 were analyzed using Google Scholar, a widely used academic search engine. The study emphasizes the significance of using AI technology to enhance Islamic scholarship through hadith studies. The primary objective is to understand the trends in AI publications related to hadith studies and identify the most commonly used AI subfields for analyzing hadith texts. The data analysis includes 29 relevant publications from credible academic sources and journals. The findings reveal fluctuations in AI-related studies on hadith, but the overall trend is declining, indicating a need for further development in this study area. Additionally, the research findings highlight that AI-related publications in Indonesia are still limited, despite being the largest Muslim-populated country. Comprehensive reference books on this topic have also not been found in the past five years. Furthermore, AI research focusing on matan studies in hadith is relatively scarce compared to sanad studies, and other AI subfields beyond Machine Learning and Natural Language Processing require more research to foster development.